Existence of Criminal Law Mechanisms in Environmental Law - Ahmad Mubarak; Ifrani Ifrani; Rahmida Erliyani; Mispansyah Mispansyah (Scholar Center, 2025)
Environmental damage in Indonesia is increasingly concerning, largely due to an anthropocentric view leading to the limitless exploitation of nature. Corporate environmental crimes often violate regulations, causing detrimental impacts on society and ecology. Despite an increase in companies engaging in pollution and environmental destruction, law enforcement against these corporations has not been optimal. Therefore, environmental impact control is crucial to minimize pollution risks. Law Number 32 of 2009 concerning Environmental Protection and Management serves as an important legal basis in Indonesia. This study employs a normative legal research method to address the urgency of criminal law instruments in environmental protection. Criminal sanctions are considered urgent and effective in tackling environmental problems as they serve as a law enforcement tool and provide a deterrent effect. The application of environmental criminal law is based on the principles of legality, sustainable development, prevention, and restraint, aiming to educate the public and prevent irresponsible behavior towards the environment.